Analisis Pengaruh Struktur Modal, Profitabilitas, Dan Intellectual Capital Terhadap Nilai Perusahaan Sebagai Dasar Keputusan Investasi - Putri Hana Ardiyanto; Jeni Susyanti; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The capital market has a large role in the economy of a country because the capital market performs 2 functions at once, namely the economic function and the financial function. In 2021, the Indonesian capital market is the highest achievement since the world was faced with the Covid - 19 Pandemic situation. Capital market activity throughout 2021 was proven by the increasing number of capital market investors reaching 7.48 million as of December 2021. From this phenomenon, the Healthcare sector is one of the 12 sectors in IDX-IC which has statistically significant development even though in 2018 – 2019 it experienced a drastic decline due to several company values that were considered overvalued. Therefore, the role of the company is very important in increasing the value of the company to attract investors and be able to compete with other competitors. The purpose of this study is to determine the effect of capital structure (DER), profitability (ROA), and intellectual capital (VAICTM) on firm value (PBV) in the Healthcare sector for the period 2019 – 2021. This study uses a quantitative method with the type of data used as secondary data. Data analysis in this study used panel data regression with EViews 12. From the test results it can be seen that the capital structure variabel has no significant effect, while the profitability and intellectual capital variabels have a significant positive effect on company value in the Healthcare sector which is listed on the Indonesia Stock Exchange for the 2019-2021 period. Keywords: capital structure, profitability, intellectual capital, company value, Healthcare sector